Peningkatan Kemampuan Literasi melalui Kegiatan “NOLITA” di Kelas 4 SDN Kemakmuran 2 - Hilda Hidansyah Agustin; Widia Nur Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Literacy is a language skill used to communicate in various ways according to specific purposes. Literacy skills include listening, speaking, reading, writing, and critical thinking. It also involves the ability to understand, utilize, and respond to information from various sources. Literacy has become one of the main focuses of the national education curriculum. However, in reality, students in Indonesia still exhibit low reading interest. Therefore, literacy improvement activities are needed, one of which is the “NOLITA” program (watching, writing, and storytelling). NOLITA is a literacy enhancement program that incorporates three main activities: watching, writing, and storytelling. This program aims to improve the literacy skills of fourth- grade students by utilizing technological advancements to attract students’ interest and concentration, particularly through watching animated videos on a smart TV. After watching, students are asked to write a summary of the story and retell it at the end of the session. A supporting medium called the